Santa's on his way - Jackson, Lisa; Yates, Maisey; Finz, Stacy; Helm, Nicole (Zebra Books / Kensington Publishing Corp., 2018)
What the cowboy wants for Christmas: When Meg O'Neill's longtime boyfriend lets her down, again, on Christmas no less, she braves an Oregon blizzard to get to her best friend Noah's comforting arms. But this time Noah's not telling her what she wants to hear--he's telling her the truth, from his heart. And his words just might be the gift Meg's been wishing for all along.